Structure and metabolism of bovine aortic proteoglycans - Murray, Eileen (Division of Biomedical Engineering, 2026)
Although a number of studies of arterial glycosaminoglycans have been carried out, there is comparatively little information available regarding the native state in which these glycosaminoglycans occur, namely covalently bound to protein to form proteoglycans. There are numerous factors that make arterial proteoglycans difficult to study, such as their relatively low concentration in the tissue a s compared to cartilaginous tissue, and their association with the fibrous elements of the matrix which make quantitative extraction difficult. In recent years reports of characterizations of arterial proteoglycans have appeared in the literature but they differ markedly in several respects. In order to minimize such variables, proteoglycans isolated from pure medial tissue of bovine aortas from different age groups have been studied. Isolation of these proteoglycans was carried out essentially as described for their counterparts from cartilage. Furthermore, proteoglycans have been isolated from a cultured clonal line of foetal bovine aortic medial smooth muscle cells and comparison s made between the two sources of material in terms of their proteoglycan monomer size and glycosaminoglycan composition.